Avaliação de uma proposta de ensino de leitura e escrita para jovens e adultos utilizando software educativo - Llausas, Rosana Valiñas (2008)
Due to high level of illiteracy in our country and the low writing and reading performance among the literate people, despite of the government investments in education, research became necessary to develop new methodology in order to reduce these indices. Researchers of behavior approach have done studies based on the paradigm of the equivalence of stimulus, with promising results for the teaching of reading and writing. The purpose of this study is the evaluation of the process of teaching to improve the reading and writing repertoire of adults that attended an educational course for young adults and adults, based on the paradigm of the equivalence of stimulus using the Mestre® (Goyos e Almeida, 1996) software as a main resource. Five pupils from EJA, a confessional institution of São Paulo, had participated. The procedure was done in different stages: 1) Evaluation of the participant previous repertoire of writing and reading, focusing on the relation between stimulus of different modalities: sound (A) pictures/ images (B) and printed words (C). 2) The teaching of relations AB, AC, CE and AE and the test of relations, BC, CB, BE and CD for words with simple syllabus. 3)Tests of generalization reading and construction of dictated words with simple syllabus, and the reading of sentences. 4)The teaching of relations AC, CE and AE, and the test of relation CD for words with complex words. 5) Administer once more the tests of generalization reading and construction of dictated words with simple syllabus, and the reading of sentences. 6) Tests of generalization reading and construction of dictated words with complex syllabus. Comparing the previous performance and the performance after the teaching procedure, it was verified that the participants with difficulty in reading and writing of simple and complex words showed emergence of an expressive oral reading and writing comprehension as well a generalization reading and writing. The participants that dominate the reading skill but have difficulty with writing showed emergence of writing, after the teaching of complex words. They also showed a generalization writing and reading of sentences with complex syllabus